Legal and Institutional Framework for Trafficking in Persons and Protection of Victims in Nigeria - Okoye, Chioma Okeoma; Okolie, Enright Que; Abonyi, Anslem Uchechukwu (Islamic Criminal Law Study Program, Bunga Bangsa Cirebon Islamic University, 2025)
This study examines the legal and institutional frameworks addressing human trafficking and victim protection in Nigeria. The study focuses on the role of national laws, institutions, and international agreements in combating human trafficking and protecting victims’ rights. The study explores key legal instruments, such as the Constitution of the Federal Republic of Nigeria 1999 (amended), the Child’s Rights Act 2004, the Penal Code 2004, the Labour Act 2004, the Criminal Code Act 2004, and the Trafficking in Persons (Prohibition) Enforcement and Administration Act 2015. In addition, the study analyzes the roles of institutions such as the National Agency for the Prohibition of Trafficking in Persons (NAPTIP), the National Human Rights Commission (NHRC), the police, and civil society organizations in prevention, law enforcement, victim rescue, and advocacy. Nigeria is also committed to international legal frameworks, including the Palermo Protocol, the Convention on the Rights of the Child, and the Convention on the Elimination of All Forms of Discrimination against Women. This study uses a qualitative approach with a systematic review based on the PRISMA framework. The study results show that despite progress, major challenges remain, such as weak law enforcement, lack of coordination between institutions, and inadequate support for victims. Therefore, strengthening legal mechanisms and improving institutional coordination are important steps to build a more effective and humane response to human trafficking in Nigeria.